Reconstruction of the Normative Legal Research Paradigm in Responding to Global Challenges: An Epistemological Analysis - Muh. Ali Masnun; Dicky Eko Prasetio; Maalikatussofa (Universitas Negeri Surabaya, 2025)
Legal research is essentially a scientific activity conducted by both academics and legal practitioners. Legal research has so far been dominated by a normative approach that focuses on internal analysis of the legal system, although its development has led to various problems. This article aims to propose a legal research paradigm to address global challenges. The analysis results show that there is an urgency to reconstruct the legal research paradigm towards a more comprehensive approach. This approach emphasizes the integration of the strengths of normative analysis with external dimensions through empirical, sociological, and interdisciplinary perspectives. The reconstruction of this paradigm is not intended to replace the normative approach, but rather to expand and enrich legal analysis to make it more contextual, adaptive, and reflective. With epistemological, methodological, and axiological renewal, the legal research paradigm is expected to drive a more substantive, just, and relevant transformation of law to meet the needs of society in the contemporary era.